Pengaruh Retaliation dan Gender Terhadap Niat Melakukan Whistle Blowing - Bagus Saputra; Sany Dwita (Universitas Negeri Padang, 2018)
This study aims to empirically examines the influence of retaliation on whistleblowing intentions, the influence of gender on whistleblowing intention, and the influence of retaliation and gender interaction on whistleblowing intention. This study used a quasi-experimentation design. The data of this study were collected by a survey questionnaires administered on 122 accounting students from a university in Padang, the capital of West Sumatra. The data were analyzed using ANOVA. The results of this study show that retaliation, and gender as well as the interaction of retaliation and gender influences individual’s whistle-blowing intention. The results have implications on the emphasis of promoting whistle-blowing among employees in public sector organizations. Keywords: retaliation, gender, and whistleblowing